2011
DOI: 10.1016/j.micres.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

ChoG is the main inducible extracellular cholesterol oxidase of Rhodococcus sp. strain CECT3014

Abstract: Cholesterol catabolism has been reported in different bacteria and particularly in several Rhodococcus species, but the genetic of this complex pathway is not yet very well defined. In this work we report the isolation and sequencing of a 9.8 kb DNA fragment of Rhodococcus sp. strain CECT3014, a bacterial strain that we here identify as a Rhodococcus erythropolis strain. In this DNA fragment we found several ORF that are probably involved in steroid catabolism, and choG, a gene encoding a putative cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Sojo et al (1997) also showed a decline in the intracellular cholesterol oxidase of R. erythropolis coupled with an increase in extracellular cholesterol oxidase, with kinetics that suggested the excretion of extracellular enzyme was due to the partial solubilization of membrane-bound cholesterol oxidase. Therefore, the results of the present study are in agreement with reports that intracellular cholesterol oxidase contributes slightly to cell growth, while extracellular cholesterol oxidase does not (Sojo et al, 1997;Fernandez de las Heras et al, 2011).…”
Section: 5supporting
confidence: 93%
See 1 more Smart Citation
“…Sojo et al (1997) also showed a decline in the intracellular cholesterol oxidase of R. erythropolis coupled with an increase in extracellular cholesterol oxidase, with kinetics that suggested the excretion of extracellular enzyme was due to the partial solubilization of membrane-bound cholesterol oxidase. Therefore, the results of the present study are in agreement with reports that intracellular cholesterol oxidase contributes slightly to cell growth, while extracellular cholesterol oxidase does not (Sojo et al, 1997;Fernandez de las Heras et al, 2011).…”
Section: 5supporting
confidence: 93%
“…6D. Unlike extracellular cholesterol oxidase, the membrane-bound enzyme is involved in cell metabolism of cholesterol, which contributes to a small degree to cell growth (Sojo et al, 1997;Fernandez de las Heras et al, 2011). The second stage in the decline of phytosterol concentration could be due to an increase in the release of extracellular cholesterol oxidase, w a t e r r e s e a r c h 5 8 ( 2 0 1 4 ) 7 1 e8 1 which has been reported to appear towards the end of the exponential growth phase (Sojo et al, 1997).…”
Section: 5mentioning
confidence: 99%
“…For the promoter growth experiments, cells were plated in minimal medium M457 plates containing the desired carbon source and incubated at 30 °C for 3 days. Cholesterol and AD were previously dissolved in methyl-β-cyclodextrin (CD) [26] and prepared as described [27]. Plasmids and bacterial strains used are listed in Additional file 1.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol oxidase indicator plates were prepared as previously described by Fernández de las Heras et al (10) by using agar and minimal medium with cholesterol dissolved in CD; plates contained 0.1 mg/ml odianisidine and 1 U/ml peroxidase. Extracellular cholesterol oxidase activity is indicated by the production of brown color in the agar medium around the colonies.…”
Section: Methodsmentioning
confidence: 99%